Zebrafish as a new model for rhododendrol‐induced leukoderma. (8th August 2021) - Hayazaki, Masumi; Hatano, Osamu; Shimabayashi, Saki; Akiyama, Takumi; Takemori, Hiroshi; Hamamoto, Akie
Abstract: Idiopathic leukoderma is a skin disorder characterized by patchy loss of skin pigmentation due to melanocyte dysfunction or deficiency. Rhododendrol (RD) was approved as a cosmetic ingredient in Japan in 2008. However, it was shown to induce leukoderma in approximately 20, 000 customers. The prediction of cytotoxicity, especially to melanocytes in vivo, is required to avoid such adverse effects. Since the use of higher vertebrates is prohibited for medicinal and toxicological assays, we used zebrafish, whose melanocytes were regulated by mechanisms similar to mammals. Zebrafish larvae were treated with RD in breeding water for 3 days, which caused body lightening accompanied by a decrease in the number of melanophores. Interestingly, black particles were found at the bottom of culture dishes, suggesting that the melanophores peeled off from the body. In addition, RT‐PCR analysis suggested that the mRNA levels of melanophore‐specific genes were significantly low. An increase in the production of reactive oxygen species was found in larvae treated with RD. The treatments of the fish with other phenol compounds, which have been reported to cause leukoderma, also induced depigmentation and melanophore loss. These results suggest that zebrafish larvae could be used for the evaluation of leukoderma caused by chemicals, including RD.